A review of Abraham Accords among Israel and the Arab Countries and its impact on Palestine: اسرائیل اور عرب ممالک کے مابین ابراہام معاہدہ اور فلسطین پر اس کے اثرات کا جائزہ - Ayub, Muhammad; Anwar, Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
Abraham Accords is actually designed by the American think tank. The ex-president of America Donald Trump take special interest in designing this accords and he give this accords the name of Abraham which accept and recognize from all three big religious followers such as Muslims, Christians and Jews. It must be clear to everyone that ex-president of America Donald Trump was Jew by religion and he visit to the Wailing Wall for the first time in the history of American presidents. He enforce all Arab countries especially Saudi Arabia to sign this accords according to his wishes. So the Arab countries will sign Abraham Accords gradually by the influences of Saudi Arabia. Abraham Accords has positive impact on the Palestine issue and Middle East well as negative impact too. In this research article all these related issues are highlighted by the researchers. The research paper has five main topics on different related issues which are discussed here. The summery, findings and recommendations are given at the end. https://doi.org/10.5281/zenodo.10519488